A compendium of temperature responses of Rubisco kinetic traits: variability among and within photosynthetic groups and impacts on photosynthesis modeling - Galmés, Jeroni (J Exp Bot, 2016)
The present study provides a synthesis of the in vitro and in vivo temperature responses of Rubisco Michaelis–Menten constants for CO(2) (K(c)) and O(2) (K(o)), specificity factor (S(c,o)) and maximum carboxylase turnover rate ([Formula: see text]) for 49 species from all the main photosynthetic kingdoms of life. Novel correction routines were developed for in vitro data to remove the effects of study-to-study differences in Rubisco assays. The compilation revealed differences in the energy of activation (∆H(a)) of Rubisco kinetics between higher plants and other photosynthetic groups, although photosynthetic bacteria and algae were under-represented and very few species have been investigated so far. Within plants, the variation in Rubisco temperature responses was related to species’ climate and photosynthetic mechanism, with differences in ∆H(a) for [Formula: see text] among C(3) plants from cool and warm environments, and in ∆H(a) for [Formula: see text] and K(c) among C(3) and C(4) plants. A negative correlation was observed among ∆H(a) for S(c/o) and species’ growth temperature for all data pooled, supporting the convergent adjustment of the temperature sensitivity of Rubisco kinetics to species’ thermal history. Simulations of the influence of varying temperature dependences of Rubisco kinetics on Rubisco-limited photosynthesis suggested improved photosynthetic performance of C(3) plants from cool habitats at lower temperatures, and C(3) plants from warm habitats at higher temperatures, especially at higher CO(2) concentration. Thus, variation in Rubisco kinetics for different groups of photosynthetic organisms might need consideration to improve prediction of photosynthesis in future climates. Comparisons between in vitro and in vivo data revealed common trends, but also highlighted a large variability among both types of Rubisco kinetics currently used to simulate photosynthesis, emphasizing the need for more experimental work to fill in the gaps in Rubisco datasets and improve scaling from enzyme kinetics to realized photosynthesis.